International Students in Higher Education: A Follow-up Study of University Graduates - Zelmer, Amy E.; Johnson, Neil A. (Canadian Journal of Higher Education, 1988)
Despite current concern about declining foreign student enrolments in Canadian post-secondary institutions, there remains a paucity of information regarding international students’ perceptions and performance after returning to their own countries. To assist in overcoming this deficiency, this paper reports about methodological procedures, results and research and policy implications from an investigation of CIDA graduates who had studied at the University of Alberta between 1972 and 1984. A range of substantive outcomes are presented: educational attainments and characteristics of students; marital and family circumstances; preferred programs of study; use of and satisfaction with university facilities; academic and personal interaction; prior and subsequent employment; adjustments to Canada; advantages and disadvantages accruing from studying in Canada; as well as comments about the experience and advice for prospective international students. The findings had policy implications relating to correction of imbalances according to gender, nationality and employment background of students, as well as to provision for academic, personal, recreational and financial needs of international students. Suggestions are also made about data collection emphases, strategies for establishing and maintaining contact with informants, and productive avenues for future inquiry.